Analisis Sistem Pengelolaan Rekam Medis di Puskesmas Sri Padang Tebing Tinggi - Cyndiandari, Amalia; Agustina, Dewi (Poltekkes Kemenkes Kendari, 2023)
To create good medical record services, it is necessary to manage good medical records in accordance with procedures and guidelines from Permenkes No. 24 of 2022 concerning Medical Records. However, based on an initial survey research, the Sri Padang Health Center did not use electronic medical records, and according to information from the Tebing Tinggi Health Office’s Data Recording and Reporting Unit, the Sri Padang Health Center was still experiencing delays in data entry and annual data reporting. This study aims to find out how the medical record management system is at the Sri Padang Tebing Tinggi Health Center. The type of qualitative research is descriptive. The research informantsconsisted of 3 main informants: namely the head of medical records, the executor of medical records, and general practitioners, the triangulation informant was 1 person, namely the head of the puskesmas. Informant selection technique with purposive sampling. Data collection techniques with interviews and observation. Research instruments with interview guidelines. The results showed that the medical record management system at the Sri Padang Health Center had not fully used the electronic medical record system, the distribution, coding, indexing, storage, and retention activities were still not optimal, especially the placement of officers, and there were obstacles in the management process, namely inadequate storage support facilities, lack of accuracy of doctors and nurses in filling out medical records, there is no skill development for substitute medical record officers and the confidentiality of medical-records is not maintained because there is no special medical record officer.